Amlodipine modulation of analgesic effect of non-steroidal anti-inflammatory drugs in rheumatoid arthritis, comorbid with arterial hypertension - N. M. Seredynska; V. I. Kornienko; D. V. Kibkalo; O. S. Suvorova; O. M. Marchenko; O. V. Ladogubets (Regulatory Mechanisms in Biosystems, 2020)
With the interaction of drugs belonging to different pharmacotherapeutic groups – nonsteroidal anti-inflammatory and antihypertensive – against the background of comorbid arterial hypertension with rheumatoid arthritis, the activity and safety of drugs may change with their combined use. Changes in the analgesic activity of nonsteroidal anti-inflammatory drugs, different in their selectivity to the types of cyclooxygenase (diclofenac, nimesulide and celecoxib), under the conditions of their long-term combined use with amlodipine in different periods of inflammation against the background of hypertension should be studied. Using the model of adjuvant arthritis comorbid with hypertension, in experiments on nonlinear mature white rats, the threshold of pain sensitivity has been determined by means of the “tail flick” test. Hypertension was caused by salt load with 1% sodium chloride solution for drinking with free access to it. Adjuvant arthritis was induced by the introduction of complete Freund’s adjuvant into the plantar aponeurosis of the hind limb of each animal with the established arterial hypertension. Against the background of arterial hypertension and comorbid pathology, there was an increase in the threshold of pain sensitivity observed in rats, which indicated the development of hypoalgesia. When combined, amlodipine enhanced the analgesic activity of diclofenac during 60 days of observation, slightly heightened the analgesic effect of nimesulide – up to 42 days, the effect of Celecoxib – in the acute period and the period of manifestation of adjuvant arthritis against the background of hypertension. The antinociceptive effect of diclofenac with amlodipine and celecoxib with amlodipine exceeded the analgesic effect of the combined nimesulide with amlodipine use against the background of comorbid pathology. The results obtained can be taken into account under the conditions of prescribing drugs belonging to the studied pharmacotherapeutic groups. It is likely that the use of diclofenac for analgesia against the background of comorbid conditions is only appropriate in the acute period of rheumatoid arthritis. The use of nimesulide to achieve an analgesic effect in the recurrence of rheumatoid arthritis against the background of hypertension is appropriate in the acute period and in the period of the inflammatory process attenuation. A highly selective coxib group cyclooxygenase-2 inhibitor, celecoxib, can reduce pain during the acute period of arthritis and during the manifestation of an inflammatory reaction that has developed against the background of arterial hypertension.